Workplace Ethical Communication and Quality Service Delivery of State-owned Tertiary Institutions, Oyo State, Nigeria - Oloye, Rachael A; Adenekan, Tolulope E (International Journal of Media and Communication Research, 2024)
Internal communications may be as ancient as the practice of communicating organizational values in the workplace. Maintaining a strong culture of compliance at work requires ethical communication. When executed properly, ethical communications may reduce total risk and improve the delivery of high-quality services. But organizations’ risk serious financial, legal, and reputational consequences when they disregard ethics. A service is efficient when the same objectives are accomplished with the help of available resources and successful when the results or accomplishments are valuable to the consumers. Quality has always been the cornerstone of any developed and successful institution around the world. However, preliminary investigations revealed that quality service delivery in State-owned tertiary institutions is on the decline. As a result, this study examined how workplace ethical communication affect the provision of high-quality services in state-owned tertiary institutions in Oyo State, Nigeria. 2,273 management employees at the top and intermediate levels from the six institutions under investigation make up the study's population. The sample size was 329 gotten from Raosoft sample size determinant. Cross sectional survey was adopted for this study. Findings revealed that work ethics significantly influence quality service delivery of State-owned tertiary institutions, Oyo State, Nigeria (Adj R2=0.628; p=0.000, Q2 =0.472). This study concluded that workplace ethical communication and its quality service delivery are inextricably linked. The study recommended that management of the selected State-owned tertiary institutions should ensure that strategies are put in place for strict compliance to ethics and positive attitude being a pre-requisite in delivering quality service